Analisis Bibliometrik Terhadap Publikasi pada Program Pengembangan Profesi Guru dalam Pembelajaran Matematika di Sekolah Dasar - Gunawan, Indra; Tatang Herman; Sumar Hendayana (Jurnal Elementaria Edukasia, 2023)
It is still uncertain whether teacher professional development is still in great demand, especially in the field of educational research. This research is aimed as preliminary research to determine the research gaps to be taken, especially those related to teacher professional development programs (PDPs) at the elementary level during last decade. The research method used was a computational mechanism using several applications such as Publish or Perish, Microsoft Excel, and VOS viewer. The number of PDP studies in mathematics learning at the elementary level during this period was 1038 but due to the limited results of the Publish and Perish software, sampling was carried out and 999 data were filtered. The results show that the trend has experienced a downgrade in the last five years, the most research in this focus was conducted in 2015 with 173 works, followed by 2013 with 170. The data showed a fluctuating trend from 2013 to 2017 before declined drastically with only 5 publications in each of the last two years. VOSviewer was used for computational mapping and showed that research opportunities for PDPs should be increased, especially at the elementary level. Based on network visualization, PDP is closely to several other keywords.